Strong but opposing effects of associational resistance and susceptibility on defense phenotype in an African savanna plant. Issue 12 (19th August 2019) - Coverdale, Tyler C.; McGeary, Ian J.; O'Connell, Ryan D.; Palmer, Todd M.; Goheen, Jacob R.; Sankaran, Mahesh; Augustine, David J.; Ford, Adam T.; Pringle, Robert M.
Abstract : The susceptibility of plants to herbivores can be strongly influenced by the identity, morphology and palatability of neighboring plants. While the defensive traits of neighbors often determine the mechanism and strength of associational resistance and susceptibility, the effect of neighbors on plant defense phenotype remains poorly understood. We used field surveys and a prickle‐removal experiment in a semi‐arid Kenyan savanna to evaluate the efficacy of physical defenses against large mammalian herbivores in a common understory plant, Solanum campylacanthum . We then quantified the respective effects of spinescent Acacia trees and short‐statured grasses on browsing damage and prickle density in S. campylacanthum . We paired measurements of prickle density beneath and outside tree canopies with long‐term herbivore‐exclusion experiments to evaluate whether associational resistance reduced defense investment by decreasing browsing damage. Likewise, we compared defense phenotype within and outside pre‐existing and experimentally created clearings to determine whether grass neighbors increased defense investment via associational susceptibility. Removing prickles increased the frequency of browsing by 25%, and surveys of herbivory damage on defended leaves suggested that herbivores tended to avoid prickles. As predicted, associational resistance and susceptibility had opposing effects on plant phenotype: individuals growing beneath Acacia canopies (or, analogously, within large‐herbivore exclosures) had a significantly lower proportion of their leaves browsed and produced 70–80% fewer prickles than those outside refuges, whereas plants in grass‐dominated clearings were more heavily browsed and produced nearly twice as many prickles as plants outside clearings. Our results demonstrate that associational resistance and susceptibility have strong, but opposing, effects on plant defense phenotype, and that variable herbivore damage is a major source of intraspecific variation in defense phenotype in this system.